Pseudomonas aeruginosa Blepharitis in a Patient with Vancomycin Induced Neutropenia - Michael A John; Thomas W Austin; Anne Marie Bombassaro (Canadian Journal of Infectious Diseases)
A patient who developed a necrotizing pseudomonas blepharitis as a complication of drug induced neutropenia is reported. Although the patient’s neutrophil count recovered and he survived his infection, radical reconstructive surgery of his eyelids was required. Clinicians should keep in mind that in patients with predisposing risk factors, even commonly encountered infections such as blepharoconjunctivitis may be caused by atypical pathogens.